STM and SFM in biology - Marti, Othmar; Amrein, Matthias (Academic Press, 1993)
STM and SFM in Biology is a book fully dedicated to biological applications of the new technology of scanning probe microscopy (SX). The scanning tunneling microscope (STM) and its first off-spring, the scanning force microscope (SFM), resolve surface topography at the atomic scale. They also detect certain electronic and mechanical properties, and perform well in ultrahigh vacuum, ambient atmosphere, and aqueous solution environments. Thus, STM and SFM offer powerful tools for biological investigations of nucleic acids, proteins, membranes, and living cells. Key Features * Introduces the reader to SXM * Presents fundamentals of STM, SFM, and other SXMs * Covers biological applications of STM and SFM * Describes experimental techniques that can be reproduced in the laboratory * Contains extended bibliographies that guide the reader to detailed source publications.